2018
DOI: 10.1515/geo-2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of limestone and dolomite tailings’ particle size on potentially toxic elements adsorption

Abstract: The aim of the study is the investigation of potentially toxic elements adsorption on limestone, dolomite and marble particles of different size. As parameters, rock particle size, solution concentration, contact time and presence of other elements in the solution have been investigated. Four fractions with different particle size (−4mm + 1mm, −1mm + 315μm, −315μm + 90μm, <90μm) have been studied. Batch experiments have been carried out at 20, 60, 120 min from monoelement and competitive Cd, Cu, Pb, Zn solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Good sorption properties of dolomite towards heavy metal cations, i.e., Pb, Cd, Zn, Cr, Cu, Sr, As, and Ba, have been confirmed by numerous studies [15,[17][18][19][20][21][22][23][24][25], including the author's study [3]. Examinations of the effect of dolomite grain size on the efficiency of the adsorption of heavy metal ions conducted by Farmaki et al [26] showed no significant relationship between their size and the level of sorption of pollutants. Therefore, when using fine-grained dolomite waste for the construction of physical and chemical barriers, it will not be necessary to grind or sieve it beforehand, which will greatly simplify the preparation of material for the construction of an isolation barrier and reduce the cost of technology.…”
Section: Introductionmentioning
confidence: 91%
“…Good sorption properties of dolomite towards heavy metal cations, i.e., Pb, Cd, Zn, Cr, Cu, Sr, As, and Ba, have been confirmed by numerous studies [15,[17][18][19][20][21][22][23][24][25], including the author's study [3]. Examinations of the effect of dolomite grain size on the efficiency of the adsorption of heavy metal ions conducted by Farmaki et al [26] showed no significant relationship between their size and the level of sorption of pollutants. Therefore, when using fine-grained dolomite waste for the construction of physical and chemical barriers, it will not be necessary to grind or sieve it beforehand, which will greatly simplify the preparation of material for the construction of an isolation barrier and reduce the cost of technology.…”
Section: Introductionmentioning
confidence: 91%
“…The hexagonal crystalline network of dolomite carbonate materials does not significantly affect the ecosystem due to its chemical composition. Farmaki et al (2018) highlighted that dolomite and carbonated materials pose no toxicity to marble and limestone. Thorough studies have demonstrated that dolomite powder contains Mono element solutions for surface complexation, ensuring its compatibility with these mineral resources.…”
Section: Possible Effects On Ecosystemsmentioning
confidence: 99%
“…The leachate generated from red mud/bauxite tailings also contains high concentrations of inorganic cations along with sulfates, and chlorides [4]. Similarly, the leachate of dolomite tailings and limestone tailings contains high concentrations of calcium ions [5][6] and, potash mining leads to the generation of tailings having high concentrations of sodium and potassium ions [7]. Mining wastes are disposed in the form of slurry in engineered disposal facilities behind the dams [8][9].…”
Section: Introductionmentioning
confidence: 99%